Слов'яни Башкортостану: розвиток пісенної культури чи стагнація? - Ахатова, Ф. (Народна творчість та етнографія, 2007)
This article is dedicated to development of song culture of the Slavonians who live in Bashkortostan. The author of the article determines value of folklore and status of musical culture of the Ukrainians and the Russians who live in this country.